Applications of Industry 4.0 during COVID-19 Situation for Thailand's Logistics System in Customer Satisfaction Context - Buranasing, Y.; Jongprasithporn, M.; Yodpijit, N. (My University, 2021)
The COVID-19 outbreak has affected business activities in many industries that can be disrupted by customer behavior. Logistics system plays the major role for response customer satisfaction. This research aims to develop logistics system in customer satisfaction context during COVID-19 situation in Thailand using Industry 4.0 principles. This paper presents the overview of Industry 4.0 and logistics system, the evaluation of customer satisfaction in logistics system during COVID-19 situation, and the applications of Industry 4.0 for logistics system in customer satisfaction context during COVID-19 situation. This study is conducted using focus group and interview with managers from large logistics service providers in Thailand. Results indicate that the use of Industry 4.0 technologies and the development of employees' skills are the potential solutions for reducing the effects of COVID-19 in logistics system. IoT, Cloud, and Big Data support all of customer satisfaction factors. It is also found that the use of appropriate Industry 4.0 technologies and the improvement of the logistics system are the critical aspects for enhancing business competitiveness during the COVID-19 pandemic.
Keywords: COVID-19; Customer Satisfaction; Industry 4.0; Logistics System